2014
DOI: 10.1080/08870446.2013.879137
|View full text |Cite
|
Sign up to set email alerts
|

Targets for primary prevention: Cultural, social and intrapersonal factors associated with co-occurring health-related behaviours

Abstract: Objective: Multiple studies have identified clusters of co-occurring healthrelated behaviours. Little is known, however, about factors associated with such clusters. This study aims to identify these factors and to assess whether their effects are in accordance with the Theory of Triadic Influence (TTI). Design: A cross-sectional study using a representative sample (N = 3497) of the Dutch population aged 19-40. Main Outcome Measures: Our data concerned 18 health-related behaviours combined in three clusters (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In modern healthcare, adherence goes beyond medication adherence, and health professionals often advise their patients to perform various other health behaviors, including, for example, doing regular blood glucose checks, increasing physical activity, or decreasing salt intake. Earlier research has also shown that health behaviors are often associated and have shared determinants [ 32 , 33 ]. This makes it plausible that interventions that aim to improve any kind of adherence may impact on various health behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In modern healthcare, adherence goes beyond medication adherence, and health professionals often advise their patients to perform various other health behaviors, including, for example, doing regular blood glucose checks, increasing physical activity, or decreasing salt intake. Earlier research has also shown that health behaviors are often associated and have shared determinants [ 32 , 33 ]. This makes it plausible that interventions that aim to improve any kind of adherence may impact on various health behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, children and adolescents vulnerable to behave in a risky manner may also have a greater tendency to drink alcohol and swell the list of negative, premature and criminal behaviors that compromise health and favor crime, addiction, among other risk behaviors, such as addictive behaviors (cocaine, cement/glue and marijuana), low risk perception of illegal drugs [31] and sexual intercourse. The study of Scalese et al [32] demonstrates that the life habits and risky behaviors of Italian school population aged 15 -19 years old, consumers of energy and energy-alcohol mixed drinks, were positively associated with: going out with friends for fun, participating in sports, experiencing physical fights/accidents or injury, engaging in sexual intercourse without protection and being involved in accidents while driving.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that specified that the TTI is better modified, found it was too complex for guidance in the field [16], complexity in analysis of the relationship between cultural and social context [17], cultural stream factors were of less significance and the levels of influence were not hierarchical [18], and further studies stated the lack of data to properly operationalize the model thus reducing its effectiveness [19, 20]. …”
Section: Discussionmentioning
confidence: 99%